Indian Self-Rule - Philp, Kenneth R. (Utah State University, University Libraries, 1995)
Now back in print, this important collection of first-hand accounts from individuals who had leading roles in Indian-white relations is a necessary reference for anyone interested in the modern Indian experience. Reviewing fifty years of Indian history since the Indian Reorganization Act was passed during FDR's New Deal administration, the contributors include Indian leaders and activists from a wide cross-section of America's varied native communities.